The transition to retirement and subsequent physical health among middle-aged and older adults in China: A life course perspective - Guodong Zhu; Dianxi Wang; Shijun Chen (PLoS ONE, 2026)
The transition from work to retirement is a critical shift in an individual’s later life. Utilizing retrospective data from the 2014 China Health and Retirement Longitudinal Study (CHARLS), this study employed sequence analysis to identify typical retirement transition patterns, followed by multiple regression analysis to examine their association with physical health. Five groups of retirement trajectories are identified: “Not Retired,” “Early Retirement,” “Late Retirement from Agricultural Employment,” “Statutory Retirement,” “Late Retirement from Self-employment”. The “Statutory Retirement” and “Early Retirement” groups typically complete their retirement transition earlier, often retiring at the statutory age with substantial pension support. In contrast, the “Not Retired,” “Late Retirement from Agricultural Employment,” and “Late Retirement from Self-employment” groups exit the labor force later in life. These individuals are primarily engaged in agricultural production or self-employment and generally lack robust pension insurance. Regression analysis found a significant association between retirement transition patterns and physical health. The “Statutory Retirement” group demonstrates lower Instrumental Activity of Daily Living (IADL) ( B = −0.393, P < 0.001), and NAGI ( B = −0.791, P < 0.001) scores. The “Late Retirement from Self-employment” group also showed lower IADL ( B = −0.356, P < 0.01) and NAGI ( B = −0.555, P < 0.001) scores. The “Early Retirement” group exhibits a lower NAGI score ( B = −0.345, P < 0.001). In contrast, the “Late Retirement from Agricultural Employment” group was associated with higher scores in Activities of Daily Living (ADL) ( B = 0.212, P < 0.05) and IADL ( B = 0.407, P < 0.01). Contact with children moderated the relationship between retirement transition and physical health. Increased intergenerational contact had a stronger positive correlation with health for individuals in the “Late Retirement from Agricultural Employment” group but showed no significant health benefit for those in the “Statutory Retirement” group.